EVALUASI MANAJEMEN PENYELENGGARAAN PEMILU SERENTAK TAHUN 2019 DAN IMPLIKASINYA - Rikson P Tampubolon (Bawaslu Provinsi Kepulauan Riau, 2019)
The electoral process that can run, but leaves a number of problems that stain the electoral process itself, must be valuablelessons for the children of this nation. Our democratic party has become a human tragedy for the ideals that began, namely efforts to give birth to new leadership. We must not consider existing problems to become routine problems. The issue of management is at the root of the problem which makes the electoral problem chaos and sets a bad precedent for the development of democracy because it has caused thousands of fatalities, even many have died from our election organizers at the forefront. Improving electoral management by taking into account the true burden of the electoral process is a necessity.Strengthening existing logistics management, so as to reduce the impact on existing problems. Increasing the understanding of election organizers, so that they avoid the chaos of the main administration in the regions. And, the most important thing needs to be a thorough evaluation related to the implementation of simultaneous elections, especially as a result of the many victims of election organizers in the regions who are victims of our democratic party.